Pengembangan Nilai-Nilai Budaya Tahlilan Berbasis Cognitive Behavioral Therapy (CBT) untuk Mengatasi Kesulitan Berkomunikasi pada Siswa SMP 01 Islam Jember - Ika Nurul Khoiria Ika; Mudafiatun Isriyah; Nailul Fauziyah (Universitas Hamzanwadi, 2026)
Communication difficulties remain a serious challenge for students in the learning process and social interactions at school. This condition can hinder students' academic, social, and emotional development if not addressed systematically. This study aims to develop an intervention based on the cultural values of tahlilan combined with a Terapi Perilaku Kognitif (CBT) (CBT) approach to address communication difficulties in students. The values of tahlilan, such as togetherness, self-reflection, spiritual tranquility, and collective prayer, are integrated with CBT principles that emphasize changes in mindset, emotional management, and reinforcement of positive behavior. This study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects were students of SMP 01 Islam Jember who were identified as having communication difficulties. Initial analysis results showed that most students experienced communication anxiety related to low self-confidence and negative mindsets. The intervention was designed with a combinatory approach, utilizing tahlilan as a structured and spiritual communication training medium. The trial results showed that this approach was able to significantly improve students' communication skills, both from the cognitive, emotional, and social behavioral aspects. The development of this intervention not only offers a contextual and religious approach, but also becomes a local culture-based solution that is applicable in the context of Islamic schools.